PREDICTION OF POST AND REPOST CONTENT ON CILETUH GEOPARK INSTAGRAM ACCOUNTS IN THE COVID-19 PANDEMIC - Agustini, Prima; Devita, Angela M; Putri, Annisa W; Virginia, Tracy (Universitas Nasional, 2021)
During this pandemic, the ease of use of the Instagram application has made it a medium of information to meet user needs, including for tourism purposes. Indonesia has many tourist destinations with the concept of sustainable tourism, one of which is the Ciletuh Geopark. Geopark Ciletuh has an Instagram account that actively posts various content. Geopark Ciletuh's Instagram account, namely @geopark_ciletuh_sukabumi uses posts and reposts as content sources. Its function is to increase the visibility of tourist destinations. This study uses a qualitative descriptive method to study the predisposition of the content of @geopark_ciletuh_sukabumi to build engagement with the audience. The purpose of this study includes a description of the difference in a post and repost content, the tone of followers' comments, and the process of diffusion of tourism ideas to the Ciletuh Geopark. The conclusion from the results of this study is that the post content on the @geopark_ciletuh_sukabumi Instagram account does not reach 100 likes in each post. Reposting content on the @geopark_ciletuh_sukabumi Instagram account has more engagement in terms of the number of likes and comments. Meanwhile, the content tone in the comment column is divided into positive tones, neutral tones, and negative tones. The process of diffusion of ideas also depends on the length of time it takes for each individual or group to adopt the idea of ​​traveling to the Ciletuh Geopark which is spread on Instagram accounts.